The Multidimensionality of Calling: Conceptualization, Measurement and a Bicultural Perspective. - Hagmaier-Göttle, Tamara; Abele, Andrea E. (Journal of Vocational Behavior, 2012)
The experience of a calling may be seen as the ultimate form of subjective career success that has many positive consequences for individuals and organizations. We are here concerned with the conceptualization of a new multidimensional measure of calling, the MCM. In the first two studies we employed a qualitative approach and came up with five core categories of the experience of a calling. Three of them could be empirically distinguished in our later quantitative studies, i.e., Identification & Person-Environment-Fit (IP), Transcendent Guiding Force (TGF), and Sense and Meaning & Value-Driven-Behavior (SMVB). We tested the reliability and validity of the MCM in two different countries (Germany and USA). Our data show that whereas TGF is most closely related to a direct calling measure, IP is more strongly related to job satisfaction. Both IP and TGF seem to have a buffering function against burnout. SMVB is endorsed most in the USA, whereas IP is endorsed most in Germany. We conclude that a multidimensional conceptualization seems appropriate in studying the experience of a calling and its consequences. (PsycINFO Database Record (c) 2013 APA, all rights reserved)
Keywords: Multidimensional Calling Measure; test development; test reliability; test validity; career success